Analysis of the effect of financial ratios on banking stock prices - Dita Anggraini (Institute of Accounting Research and Novation (IARN), 2022)
This study used bank samples, namely Bank Mandiri, Bank Rakyat Indonesia, Bank Negara Indonesia, and Bank Central Asia. By using purposive sampling method. The analytical method used is the independent sample t test using eviews version 8.0. The results of the analysis show that during the 2008-2012 observation period, CAR has an effect on stock prices because the probability value is 0.0066 < the significance level is 0.05. NPL has no effect on stock prices because the probability value is 0.8733 > the significance level is 0.05. ROE affects stock prices because the probability value is 0.0104. < from the significance level of 0.05. GWM has no effect on stock prices because the probability value is 0.3984> from the significance level of 0.05. LDR has no effect on stock prices because the probability value is 0.0988 > the significance level is 0.05. EPS affects stock prices because the probability value is 0.0000 < the significance level is 0.05. PER also affects stock prices because the probability value is 0.0000 < the significance level is 0.05. The f test shows that the CAR, NPL, ROE, GWM, LDR, PER, and EPS variables jointly affect the stock prices of banking companies in the BUKU 4 category found in the LQ-45 Index for the 2008-2012 period. Proven value of probability (F-statistic) is 0.000000. Using an alpha of 0.05 shows that the probability (F-statistic) is smaller than 0.05 (5 percent).